Effectiveness of Community Participation in the Development Planning of the Merah Putih Cooperative in the Sukalaksana Neighborhood - Adelia Rismayani; Laeli Nur Khanifah; Siti Dinda Rahayu; Tri Nurul Aida (Anthroposia: Journal of Social and Human Development, 2026)
The Merah Putih Cooperative Program was introduced to strengthen local economic development through community-based cooperative institutions. This study examines the effectiveness of community participation in the development planning of the Merah Putih Cooperative in Sukalaksana Neighborhood, Curug District, Serang City. An empirical qualitative approach with a single instrumental case study design was employed. Data were collected through semi-structured interviews, non-participant observations, document analysis, and literature review, and analyzed using Bintoro Tjokroamidjojo's development planning framework covering plan formulation, program formulation, implementation, supervision, and evaluation. The findings indicate that the planning process incorporated local economic potential, development objectives, and collaborative business strategies, although community participation remained limited during the initial planning stage due to the top-down nature of the program. Program implementation was constrained by limited capital, inadequate cooperative literacy, incomplete operational facilities, and uneven institutional support. Supervision was conducted through internal and external mechanisms, while the evaluation highlighted organizational readiness and community engagement as the primary determinants of future effectiveness. The study concludes that strengthening participatory governance, institutional capacity, and public involvement is essential for improving the long-term sustainability of the Merah Putih Cooperative.